Which investors support the transition toward a low-carbon economy? Exit and Voice in mutual funds - Jonas Zink (Journal of Asset Management, 2024)
Reducing portfolio carbon footprints (Exit) and voting in favor of climate-related shareholder proposals (Voice) are among the main actions that investors can take to promote an accelerated transition toward a low-carbon economy. This paper studies three important investor groups that can be instrumental in driving the transition and evaluates their Exit and Voice behavior. I find that the five largest asset managers perform poorly on Exit and Voice over the full sample period but improved on both in more recent years. Only a small fraction of signatories to sustainable investor initiatives are supportive of the transition. Counterintuitively, investors who perform poorly on Exit, perform well on Voice. Finally, I examine the financial consequences of employing Exit and Voice and find that Exit is positively related to risk-adjusted fund returns; however, this is not necessarily attributable to superior skill of fund managers.
Keywords: D22; G11; G23; Q51; Q54; 330; Exit; Voice; Mutual funds; Climate change; Transition; Fund performance